(untitled) (Orthodontic Journal of Nepal, 2013)
Objective: To assess periodontal status of the patients undergoing orthodontic treatment and to compare periodontal health of patients with and without orthodontic treatment. Materials & Method: A cross sectional study was done on 100 patients (50 orthodontic and 50 non-orthodontic). CPITN (Community Periodontal Index for Treatment Need) was used to assess the periodontal health of indexed teeth. SPSS version 17 and Chi Square test were used to analyze and compare the data. Result: There was a statistically significant association in CPITN score between orthodontic and non-orthodontic patients (p<0.01). Conclusion: Patients undergoing orthodontic treatment have increased plaque accumulation and probing depth that may be associated with periodontal destruction. Patient motivation to maintain oral hygiene and regular scaling will minimize hazardous effects in orthodontic patients. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9278 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 26-30